Effect of Light Intensity on the Degree of Conversion of Dual-cured Resin Cement at Different Depths with the use of Translucent Fiber Posts - Bahari, Mahmoud (J Dent (Tehran), 2014)
OBJECTIVES: To evaluate the effect of different light intensities on the degree of conversion (DC) of dual-cured resin cement at different depths of translucent fiber posts. MATERIALS AND METHODS: Thirty translucent fiber posts were randomly assigned into three (n=10) groups. They were cemented in the simulated canal spaces using Duo-Link dual-cured resin cement. The cement was light-cured under 600, 800 and 1100 mW/cm(2) light intensities for 40 seconds. DC of the resin cement was calculated at cervical, middle and apical thirds using the spectra of FT-Raman spectrometer. Data were analyzed by repeated measurement ANOVA and Tukey’s post hoc tests (α=0.05). RESULTS: In all the groups, the least DC was obtained at the apical region. There were no significant differences in the DC with different light intensities between the cervical and middle regions (p>0.05). However, in the apical region, the DC in both 800 and 1100 mw/cm(2) was similar (p>0.05), but greater with 600 mW/cm(2) light intensity (p=0.02 and p<0.001, respectively). CONCLUSION: In comparison with the light intensity of 600 mW/cm(2), the light intensity of 800 mW/cm(2) significantly increased the DC of dual-cured resin cement in the apical region. However, DC was not significantly different between 800 and 1100 mw/cm(2) light intensities. If the resin cement, especially in the apical areas is not sufficiently cured, microleakage might increase and post retention might be jeopardized. In comparison with 600 mW/cm(2) light intensity, 800 mW/cm(2) significantly increases DC at the apical third that might be clinically beneficial.